2015
DOI: 10.12659/msm.893430
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Role of PMP22 Gene in the Proliferation and Invasion of Osteosarcoma

Abstract: BackgroundAs the most common primary bone tumor, osteosarcoma has an improved survival rates with advancement of treatment methods. A higher rate of metastasis, however, leads to the aggravation of the disease. Studies have shown that some genes, namely osteosarcoma metastasis-related genes, participate in the process of tumor metastasis. The peripheral myelin protein 22 (PMP22) gene has recently been found to be abundantly expressed in the oncogenesis of osteosarcoma. Its detailed role and function in the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…To confirm the promotion of overexpressed IGF-1R on tumor cell proliferation, we referred to previous studies [ 16 , 17 ] and detected the IGF-1R expression in MG63 cells. We found that LTC treatment obviously inhibited IGF-1R expression in MG63 cells, similar to results of siRNA silencing IGF-1R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the promotion of overexpressed IGF-1R on tumor cell proliferation, we referred to previous studies [ 16 , 17 ] and detected the IGF-1R expression in MG63 cells. We found that LTC treatment obviously inhibited IGF-1R expression in MG63 cells, similar to results of siRNA silencing IGF-1R.…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic level, previous research [ 15 ] has shown that many genetic and epigenetic agents are involved in tumor pathogenesis and progression. According to Liu et al [ 16 ], PMP22 (peripheral myelin protein 22) was found to be overexpressed in osteosarcoma. The in vivo experiments proved the relationship between PMP22 and the proliferation, migration, invasion, and colony formation of osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma (OS) is an important cause of cancer-correlated deaths worldwide. OS progression is a complex, multistep process involving numerous abnormal genes and proteins [ 20 , 21 ]. The combination of local radiotherapy/chemotherapy and surgery is currently the main anti-tumor therapy, but treatment fails in many patients, in part due to resistance to chemotherapeutic agents [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have mainly focused on individual gene-related analyses (Rosemann et al, 2014;Liu and Chen, 2015;Zeng and Xu, 2015;Li et al, 2016). However, these do not accurately reflect the interaction between integral genes under different conditions (Slonim, 2002).…”
Section: Introductionmentioning
confidence: 99%